2021
DOI: 10.1002/mds.28766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Coronavirus Disease 2019 Pandemic on Motor Symptoms in Parkinson's Disease: An Observational Study

Abstract: It is becoming clear that many patients with Parkinson's disease (PD) are experiencing subjective worsening of motor symptoms during the coronavirus disease 2019 (COVID-19) pandemic. 1 However, little evidence using established quantitative scales is available on longitudinal changes in motor symptoms during the pandemic. We therefore evaluated changes in Movement Disorder Society Unified Parkinson's Disease Rating Scale, Part III (MDS-UPDRS-III), scores during the pandemic.We included PD patients who continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Although our data support previous reports on increasing symptom burden, it also documents the long-lasting deterioration that spans periods of low SARS-CoV-2 incidence rates and minimum disease control restrictions. Similar to patient-reported worsening, trend analyses of motor symptoms (Movement Disorder Society-Sponsored Revision of the Unified Parkinson's Disease Rating Scale [MDS-UPDRS] part III) revealed a worsening for 40% of PwP 23 since pandemic onset and doubled disease progression rates (MDS-UPDRS part III points/year) compared to pre-pandemic 15 . However, PwP in this study were mostly selfsufficient with few comorbidities and represent a less severely affected subgroup within the spectrum of PwP in Germany.…”
Section: Discussionmentioning
confidence: 82%
“…Although our data support previous reports on increasing symptom burden, it also documents the long-lasting deterioration that spans periods of low SARS-CoV-2 incidence rates and minimum disease control restrictions. Similar to patient-reported worsening, trend analyses of motor symptoms (Movement Disorder Society-Sponsored Revision of the Unified Parkinson's Disease Rating Scale [MDS-UPDRS] part III) revealed a worsening for 40% of PwP 23 since pandemic onset and doubled disease progression rates (MDS-UPDRS part III points/year) compared to pre-pandemic 15 . However, PwP in this study were mostly selfsufficient with few comorbidities and represent a less severely affected subgroup within the spectrum of PwP in Germany.…”
Section: Discussionmentioning
confidence: 82%
“…Increased pain may similarly result from increased anxiety but could also be caused by rigidity. Fatigue is a well-known consequence of psychological distress in PD [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, over 40% of respondents of a smaller sample from India reported worsening of PD-related symptoms after 3 weeks of restrictions [ 35 ]. Moreover, 40% of people with PD showed an intensification of motor symptoms in an observational study conducted with the use of the MDS-UPDRS III in Tokyo [ 36 ]. In contrast, a study by Guo et al revealed that almost 80% of patients reported new or worsening PD symptoms during the pandemic, and the change was significantly more severe than at baseline (pre-pandemic period).…”
Section: Discussionmentioning
confidence: 99%